Prometeo, Casal y Moreau - Fuente Ballesteros, Ricardo de la, 1955- (2013)
Este trabajo presenta el mito de Prometeo en Casal y Moreau, así como la relación entre ellos y la traslación del cuadro al poema. Por otro lado, se muestra como el común paradigma entre ellos explica las coincidencias existentes entre ambos, así como el interés del poeta por la obra del pintor.
This article introduces the myth of Prometheus in Casal and Moreau´s work, the relationship between both artist and the representation of the picture in a poetic form. This article proves a common paradigm between the artist and how this paradigm explains the existing simila- rities for both artist. Furthermore, it reveals the interest of the poet in Moreau’s paintings.
Keywords: Prometeo (Personaje mitológico); Mito; Prometeo (Personaje mitológico)